An Analysis of Lexical Cohesion on The Textbook at The Seventh Grade of Junior High School - Siska Hotnaida Malau; Sahat Taruli Siahaan; Usman Sidabutar (STABN RADEN WIJAYA WONOGIRI, 2025)
This study aims to investigate the use of lexical cohesion in creating textual coherence in seventh-grade English textbooks. The objectives of this study were to identify, analyze, and determine the dominant types of lexical cohesion used in the textbooks, with the hope of providing insights and benefits for teachers and students in the English learning process. The theoretical framework refers to Halliday and Hasan’s (1976) classification of lexical cohesion, which consists of reiteration (repetition, synonymy, antonymy, hyponymy, meronymy) and collocation. This study employed a descriptive qualitative approach, using Miles and Huberman’s (2014) model of data condensation, data display, and verification. The results showed six types of lexical cohesion were found in the textbooks, with repetition being the most dominant type (40%), followed by synonymy, antonymy, hyponymy, meronymy, and collocation (32%). These findings indicate that the textbooks emphasize vocabulary reinforcement and thematic continuity to support students’ word recognition and reading comprehension. It is concluded that lexical cohesion enriches vocabulary mastery and enhances text coherence; therefore, teachers are encouraged to utilize lexical cohesion—especially repetition and collocation—as an effective strategy for teaching English